Optimized sgRNA design to maximize activity and minimize off-target effects of CRISPR-Cas9 - Doench, John G.; Fusi, Nicolo; Sullender, Meagan; Hegde, Mudra; Vaimberg, Emma W.; Donovan, Katherine F.; Smith, Ian; Tothova, Zuzana; Wilen, Craig; Orchard, Robert; Virgin, Herbert W.; Listgarten, Jennifer; et al. (nature biotechnology, 2016)
CRISPR-Cas9–based genetic screens are a powerful new tool in biology. By simply altering the sequence of the single-guide RNA (sgRNA), one can reprogram Cas9 to target different sites in the genome with relative ease, but the on-target activity and off-target effects of individual sgRNAs can vary widely. Here, we use recently devised sgRNA design rules to create human and mouse genome-wide libraries, perform positive and negative selection screens and observe that the use of these rules produced improved results. Additionally, we profile the off-target activity of thousands of sgRNAs and develop a metric to predict off-target sites. We incorporate these findings from large-scale, empirical data to improve our computational design rules and create optimized sgRNA libraries that maximize on-target activity and minimize off-target effects to enable more effective and efficient genetic screens and genome engineering.